English Conversation Class (ECC) Untuk Menciptakan English Environment Di SMA Islam Nusantara (SMAINUS) - Kurniasih Kurniasih; Nuse Aliyah Rahmati; Atik Umamah; Diah Retno Widowati (Jurnal Inovasi Hasil Pengabdian Masyarakat (JIPEMAS), 2019)
The teaching of English in Indonesia has been started from elementary school until university level because students are expected to have good knowledge of English as the international language. In order to compete with people all over the world, English learners should be able to use English both in written and spoken form. The teaching of English in SMAINUS has been conducted in a fun way supported by the innovative teacher and interactive technique. Consequently, students have positive perceptions toward English and are more motivated to improve their English. However, there is no any English club, especially on English Conversation Club (ECC) that can facilitate students to do speaking practice outside the class to improve their productive skill rapidly. Therefore, this program is the starting point of ECC in SMAINUS. This paper aims at exploiting students’ perceptions of ECC program to create English environment.